Surgical treatment of enterovirus D68 brainstem encephalitis-induced dysphagia. Issue 5 (October 2018) - Togashi, Takafumi; Baba, Hironori; Kitazawa, Meiko; Takahashi, Nao; Samejima, Yasuhiro; Yumoto, Eiji; Horii, Arata
Abstract: Cluster of acute flaccid paralysis and cranial nerve dysfunction was associated with a 2014 outbreak of enterovirus D68 (EV-D68) respiratory illness in US. We describe a 33 year-old male patient of refractory dysphagia due to EV-D68-induced brainstem encephalitis successfully treated by surgery. Following acute upper respiratory tract infection, he developed dysphagia and bilateral facial paralysis. A coughing reflex was readily produced when the laryngopharyngeal fiberscope touched the epiglottis, however, water infusion induced only very weak and slow swallowing reflex, suggesting that only motor component was impaired but sensory function was preserved during swallowing. Despite eight months-conservative rehabilitations, Food Intake Level Scale (FILS) remained level 4. Therefore, corrective surgeries including cricopharyngeal myotomy, laryngeal suspension, and pharyngeal flap were performed. Thirty-six days after surgery, FILS rapidly and dramatically improved to level 8. This is the first report describing a successful surgical intervention for EV-D68-induced refractory dysphagia. Surgical treatment was suitable for EV-D68-induced dysphagia, perhaps because sensory function was preserved and only motor disturbance was present during the pharyngeal stage of swallowing.